Spatial tissue proteomics reveals distinct landscapes of heterogeneity in cutaneous papillomavirus-induced keratinocyte carcinomas - Schäfer, Miriam; Schneider, Martin; Müller, Torsten; Franz, Natascha; Braspenning-Wesch, Ilona; Stephan, Sonja; Schmidt, Gabriele; Krijgsveld, Jeroen; Helm, Dominic; Rösl, Frank; Hasche, Daniel (Journal of medical virology, 2023)
Infection with certain cutaneous human papillomaviruses (HPV), in conjunction with chronic ultraviolet (UV) exposure, are the major cofactors of non-melanoma skin cancer (NMSC), the most frequent cancer type worldwide. Cutaneous squamous cell carcinomas (SCCs) as well as tumors in general represent three-dimensional entities determined by both temporal and spatial constraints. Whole tissue proteomics is a straightforward approach to understand tumorigenesis in better detail, but studies focusing on different progression states toward a dedifferentiated SCC phenotype on a spatial level are rare. Here, we applied an innovative proteomic workflow on formalin-fixed, paraffin-embedded (FFPE) epithelial tumors derived from the preclinical animal model Mastomys coucha. This rodent is naturally infected with its genuine cutaneous papillomavirus and closely mimics skin carcinogenesis in the context of cutaneous HPV infections in humans. We deciphered cellular networks by comparing diverse epithelial tissues with respect to their differentiation level and infection status. Our study reveals novel regulatory proteins and pathways associated with virus-induced tumor initiation and progression of SCCs. This approach provides the basis to better comprehend the multistep process of skin carcinogenesis.
Online veröffentlicht: 15. Juni 2023
Gesehen am 02.10.2023